Faktor-Faktor Yang Mempengaruhi Prestasi Belajar Mahasiswa Program Studi Akuntansi di STIE AAS Surakarta - Budiyono Budiyono; LMS Kristiyanti (ITB AAS INDONESIA, 2020)
Accounting students have a fairly strong relationship with the problem to be studied, so researchers use accounting students as research subjects. The ethical attitude of accounting students is considered important because accounting students as prospective accountants, auditors, or managers cannot be separated from accounting practices in the world of work. The purpose of this study was to determine the effect of emotional intelligence (EQ) on the academic achievement of students majoring in accounting at AAS Surakarta. To determine the effect of intellectual intelligence (IQ) on student achievement in accounting majors at AAS Surakarta. To find out there is an influence of emotional intelligence (EQ) and intellectual intelligence (IQ) together on the academic achievement of students majoring in accounting at AAS Surakarta. The research method used is quantitative research methods. Data collection techniques using a questionnaire. Research location at STIE AAS Surakarta. The population used by accounting students is STIE AAS. Data analysis technique uses multiple linear regression. The results of the study contained a positive effect on emotional intelligence on student achievement in accounting at STIE AAS in Surakarta. There is a positive influence of intellectual intelligence on academic achievement of students majoring in accounting at STIE AAS in Surakarta. There is an influence of emotional intelligence and intellectual intelligence together on the academic achievement of students majoring in accounting at STIE AAS Surakarta.